Physico‐Chemical Processes. (1st October 2016) - Hua, Bin; Xiong, Huixin; Zhu, Guocheng; Wang, Lei; Yan, Sen; Yang, John; Deng, Baolin
Abstract : This review is on the research literature published in 2015 related to the physico‐chemical processes for water and wastewater treatment. The review is divided into six sections, including filtration, sedimentation, coagulation/flocculation, flotation, oxidation, and adsorption.